Living with a Wild God: A Nonbeliever's Search For The Truth About Everything - Ehrenreich, Barbara (New York: Hachette Book Group, Inc., 2014)
"In middle age, Ehrenreich came across the journal she had kept during her tumultuous adolescence and set out to reconstruct that quest, which had taken her to the study of science and through a cataclysmic series of uncanny-or as she later learned to call them, "mystical"-experiences. A staunch atheist and rationalist, she is profoundly shaken by the implications of her life-long search. Part memoir, part philosophical and spiritual inquiry, LIVING WITH A WILD GOD brings an older woman's wry and erudite perspective to a young girl's uninhibited musings on the questions that, at one point or another, torment us all. Ehrenreich's most personal book ever will spark a lively and heated conversation about religion and spirituality, science and morality, and the "meaning of life." Certain to be a classic, LIVING WITH A WILD GOD combines intellectual rigor with a frank account of the inexplicable, in Ehrenreich's singular voice, to produce a true literary achievement"--
Keywords: Women authors, American -- Biography; Self-actualization (Psychology) -- Biography; Philosophy and religion -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / Women